INHERITED DYSLIPIDAEMIC DISORDERS CONTRIBUTING TO CORONARY HEART DISEASE - Attaullah, Salma; Bangash, Rahim; ullah, Aman; Ahmed, Zahoor; Rehman, Jamilur (Journal of Ayub Medical College Abbottabad, 2008)
Background: Lipoprotein (a) [Lp (a)] is an established independent risk factor for premature myocardial infarction (MI)/coronary artery disease (CAD). The study was conducted to determine the value of Lp (a) in prediction of CAD or MI in the offspring at risk. Methods: A total of 160 subjects were investigated. Serum Lp (a) was measured by ELISA, serum total cholesterol, triglycerides (TG) and HDL-Cholesterol by enzymatic colorimetric methods using standard kits. Results: Differences in levels of total Lp (a) and cholesterol were observed between patients and controls. Both Lp (a) (16.23±1.95 mg/dL) and cholesterol (175.00±7.60 mg/dL) of group A (patients) were higher than the corresponding controls. However an opposite trend in results was noted for serum HDL-Cholesterol in patients vs. controls. Conclusion: Persons found to have elevated levels of Lp (a) should focus on controlling the known modifiable risk factor for heart disease, especially smoking, hypercholesterolemia, obesity, hypertension and sedentary life style. Keywords: Dyslipidaemia, Coronary Artery Disease, CAD, Lipoprotein (a), Myocardial Infarction, MI, Cholesterol, HDL-Cholesterol, LDL-Cholesterol, Triglycerides